Sinergi Edukasi TBC, PD3I, dan Imunisasi untuk Mendukung Kesehatan Lingkungan di Masyarakat Desa Peurumping Aceh Besar - Khairuman Khairuman; Rahmad Triansyah; Aldi Mahlul Rizki (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service project was conducted in Peurumping Village, Montasik District, Aceh Besar, to strengthen public knowledge and awareness regarding tuberculosis (TB) prevention, vaccine-preventable diseases (VPDs), and the role of immunization in the context of environmental health. The activity applied participatory methods, including interactive lectures, group discussions, structured questionnaires for 40 respondents, and observational engagement with local communities. Findings indicated that 60% of participants strongly supported TB prevention efforts, and 62.5% agreed with immunization programs, although 27.5% still rejected immunization. Environmental conditions such as poor ventilation (35%), high humidity (40%), and limited access to clean water (30%) were identified as factors exacerbating disease transmission. The program successfully enhanced the capacity of local health cadres, village midwives, youth groups, and local officials in promoting sustainable health education. It is concluded that community-based health education, coupled with participatory approaches, plays a vital role in improving community awareness, empowering health cadres, and fostering government commitment to advancing health behavior and environmental sanitation.